Revival and Reinvention in India’s Kathak Dance - Walker, Margaret (MUSICultures, 2010)
Although Euro-American musical revivals are usually connected to folk music, the postcolonial Indian revival privileged “classical” music and dance as objects of priceless national heritage. Yet, the revival in India was not a straightforward process of cultural recovery in the wake of occupation. Issues of authority, authenticity and appropriation are woven into the process of reclamation. Through a comparison of this period in Indian dance history with themes in current theories of revival, this article moves towards a model of “revival” as a global phenomenon seeking to broaden our understanding of cultural continuity and change.